Synthesis and anticancer activity of ethyl 5‐amino‐1‐N‐substituted‐imidazole‐4‐carboxylate building blocks. Issue 9 (25th May 2021) - Ruzi, Zukela; Nie, Lifei; Bozorov, Khurshed; Zhao, Jiangyu; Aisa, Haji A.
Abstract: A series of 5‐amino‐1‐ N ‐substituted‐imidazole‐4‐carboxylate building blocks was synthesized and assayed for their antiproliferative potential against human cancer cell lines, including HeLa (cervical), HT‐29, HCT‐15 (colon), A549 (lung), and MDA‐MB‐231 (breast) cells. The preliminary screening results revealed that several derivatives containing alkyl chains at the N‐1 position of the imidazole core demonstrate a certain inhibitory effect on growth and proliferation. A significant effect was observed following ethyl 5‐amino‐1‐dodecyl‐1 H ‐imidazole‐4‐carboxylate (5e ) treatment for 72 h. The IC50 value for HeLa cells was 0.737 ± 0.05 μM, whereas that for HT‐29 cells was 1.194 ± 0.02 μM. Further investigations revealed that 5e significantly inhibited tumor cell colony formation and migration, and it exhibited antiadhesive effects on HeLa cells as well as antitubulin activity along with the induction of early apoptosis of HeLa and HT‐29 cells. In addition, derivative 5e significantly reduced the cell mitochondrial membrane potential in a dose‐dependent manner and induced early apoptosis of HeLa and HT‐29 cells, indicating that 5e may serve as a lead compound for further drug discovery and development. Abstract : A series of 5‐amino‐1‐ N ‐substituted‐imidazole‐4‐carboxylate building blocks was synthesized and assayed for their antiproliferative potential against human cancer cell lines. Derivatives containing alkyl chains at the N‐1 position of the imidazole core demonstrate a certain inhibitory effect on growth and proliferation. A significant effect was observed following treatment with ethyl 5‐amino‐1‐dodecyl‐1 H ‐imidazole‐4‐carboxylate (5e ), which also reduced the mitochondrial membrane potential in a dose‐dependent manner.